2021
DOI: 10.1163/24714607-bja10038
|View full text |Cite
|
Sign up to set email alerts
|

The Collective Organization of Delivery Workers in Brazil during the covid-19 Pandemic: A View Based on Social Media

Abstract: This essay presents the results of a study on the work organization of food-delivery workers that use digital platforms in Rio de Janeiro, Brazil. The covid-19 pandemic exacerbated and increased the visibility of the precarious work conditions experienced by these workers, who have organized collectively throughout Brazil to demand better conditions. Based on the field of workers’ health and sociological analyses of work’s uberization, the study used a qualitative methodology with a data survey in online socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…Abilio, Grohmann, and Weiss (2021) contend that labor management, control mechanisms and strategies employed by platform companies, such as Loggi, Rappi, and iFood, result in extended working hours, meager compensation per hour worked, a lack of labor rights, minimal support from the companies for the workers, and, frequently, unexplained terminations. Strecker et al (2021) corroborate these findings, shedding further light on the precarious working conditions faced by food delivery workers who rely on digital platforms in Rio de Janeiro.…”
Section: The Brazilian Platform Economy: Case Studies and Sub-topicssupporting
confidence: 71%
See 1 more Smart Citation
“…Abilio, Grohmann, and Weiss (2021) contend that labor management, control mechanisms and strategies employed by platform companies, such as Loggi, Rappi, and iFood, result in extended working hours, meager compensation per hour worked, a lack of labor rights, minimal support from the companies for the workers, and, frequently, unexplained terminations. Strecker et al (2021) corroborate these findings, shedding further light on the precarious working conditions faced by food delivery workers who rely on digital platforms in Rio de Janeiro.…”
Section: The Brazilian Platform Economy: Case Studies and Sub-topicssupporting
confidence: 71%
“…The first stream pertains to a specific facet of the ongoing process of platformization in the country -the transformation of labor conditions, with a specific focus on food delivery workers and their collective organization (ABILIO; GROHMANN;WEISS, 2021;STRECKER et al, 2021). Abilio, Grohmann, and Weiss (2021) contend that labor management, control mechanisms and strategies employed by platform companies, such as Loggi, Rappi, and iFood, result in extended working hours, meager compensation per hour worked, a lack of labor rights, minimal support from the companies for the workers, and, frequently, unexplained terminations.…”
Section: The Brazilian Platform Economy: Case Studies and Sub-topicsmentioning
confidence: 99%
“…This study offers meaningful implications for theorizing networked organizing among social media creators. Building from work on platform labor organizing and entrepreneurial solidarities (O’Meara, 2019; Soriano & Cabañes, 2020; Strecker et al, 2022), I found that some Twitch streamers were ephemerally networked in their responses to ongoing waves of networked harassment for months but perhaps more importantly identified elements that hindered networked responses across the site’s streamers. As harassment and online attacks become more prevalent among creator communities on social media, networks of connection and disconnection form among creators, their audience communities, and governance of and by platform companies.…”
Section: Discussionmentioning
confidence: 99%
“…Social media creators and the wider public at large have slowly begun to acknowledge the legitimacy of creator labor. Despite this shifting sentiment, creators have not yet followed other groups of platform workers in forming collectives as a class of workers to demand fairer pay, reform of their payment and evaluation systems, and with some exceptions, organizing strikes (e.g., food delivery drivers in Brazil; see Strecker et al, 2022). Social media groups are commonly used to organize workers—particularly those workers geographically isolated from each other—and “enable them to manage the ambiguities of their experiences of marginality” (Soriano & Cabañes, 2020, p. 8).…”
Section: Labor and Vulnerability In Live Streamingmentioning
confidence: 99%
“…É difícil escapar de uma tendência ao individualismo, quando se está de frente com as lutas cotidianas para conseguir satisfazer as necessidades imediatas da família e pagar as contas. Há também solidariedade, tanto na reprodução cotidiana da vida e do trabalho (Alvarez et al, 2021) quanto na conquista de direitos sociais, com movimentos como o Breque dos Apps (Strecker et al, 2021;Abílio, Grohmann & Weiss, 2021), porém, ela não se constrói facilmente. As empresasplataformasss atuam na produção de divergências, seja na promoção da concorrência por meio de bonificações e na classificação dos trabalhadores, conforme seus critérios de desempenho e sistema de avaliação; seja no estímulo à ideia de meritocracia, segundo a qual a luta por direitos, muitas vezes, é tomada como vagabundagem.…”
Section: Direito Ao Público Ao Trabalho E à Saúdeunclassified